2010
DOI: 10.1017/s0950268810000841
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Legionnaires' disease associated with a supermarket mist machine

Abstract: An outbreak of Legionnaires' disease affected 12 customers of a supermarket in a town in Catalonia, Spain, between August and November 2006. An epidemiological and environmental investigation was undertaken. Preliminary investigation showed that all patients had visited the same supermarket in this town where a mist machine was found in the fish section. Water samples were collected from the machine and from the supermarket's water distribution system when high-risk samples were excluded. Environmental samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Since then, several outbreaks linked to a variety of aerosol-producing devices, such as cooling towers ( 10 – 13 ), whirpool spas ( 14 ), decorative fountains ( 15 ), mist machines ( 16 , 17 ) and industrial air scrubbers ( 18 ), have been reported. The largest outbreak of the disease (449 confirmed cases) was attributed to cooling towers in a city hospital in Murcia, Spain, in July 2001 ( 10 ).…”
mentioning
confidence: 99%
“…Since then, several outbreaks linked to a variety of aerosol-producing devices, such as cooling towers ( 10 – 13 ), whirpool spas ( 14 ), decorative fountains ( 15 ), mist machines ( 16 , 17 ) and industrial air scrubbers ( 18 ), have been reported. The largest outbreak of the disease (449 confirmed cases) was attributed to cooling towers in a city hospital in Murcia, Spain, in July 2001 ( 10 ).…”
mentioning
confidence: 99%
“…Many factors may have their own 'weight' when speaking of biologic and chemical aerosols in dimensionally limited and environmentally insulated areas such as supermarkets, hypermarkets (Barrabeig et al 2010;Wierzbicka et al 2009) and shopping centres (Lee et al 2012;Nunes et al 2005), including also • Exposure areas of food-contact surfaces (including walls and ceilings) and unpackaged/intermediate foods in high care areas; • The peculiar flow of food processing (one direction only should be preferable); • The number of moving machinery parts, including hand trucks, different carriages, fork lifts, etc. ; • The number of working operators (blue workers should be always considered as moving food-contact surfaces); • The correct procedure of washing in food processing plants (the higher the amount of sprayable water, the higher the potential formation of aerosolised suspensions with or without living microorganisms).…”
Section: Food-contact Materials and Machinery: An Overviewmentioning
confidence: 99%
“…If the stability of such a characteristic is known, then the degree to which different microbes found in an outbreak are related can be estimated [2,3]. This makes the technique very helpful in attributing or discharging sources to an outbreak [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%